The Social Intervention for Adolescence with Autism Spectrum Disorder (ASD): A Systematic Review - Faqihul Muqoddam; Wiwin Hendriani (Universitas Ahmad Dahlan, 2019)
AbstractThe systematic review aims to find the types of effective social interventions applied to adolescents with autism spectrum disorders (ASD) in several articles selected through the screening process in 2010-2018. The review was conducted with search keywords